1990
DOI: 10.3323/jcorr1974.39.1_3
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Type SUS 304 Stainless Steels Containing Tin in Organic Acid Solutions

Abstract: The effects of alloying elements, Sn and Cu, on the corrosion behavior of austenitic stainless steel of type 304 have been investigated by electrochemical techniques aqueous solutions of organic acids as food additive. Corrosiveness of lactic acid to type SUS 304 steel was stronger than that of other organic acids. The corrosion rate of the steel in boiling aqueous solution of lactic acid was reduced by addition of less than 0.5% Sn to the steel, and was further reduced by simultaneous addition of Sn and Cu. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The corrosion resistance of hot-pressed sintered stainless steel was substantially improved by Sn addition. Osozawa et al 15 and Takizawa et al 16 observed the positive synergy of Cu and Sn on the corrosion resistance of austenitic stainless steel in dilute sulfuric and organic-chlorinated acid mediums. They found that stable lms of metallic copper and tin oxides were formed on the surface of steel, which led to the preferential dissolution of Cu and Sn.…”
Section: Introductionmentioning
confidence: 98%
“…The corrosion resistance of hot-pressed sintered stainless steel was substantially improved by Sn addition. Osozawa et al 15 and Takizawa et al 16 observed the positive synergy of Cu and Sn on the corrosion resistance of austenitic stainless steel in dilute sulfuric and organic-chlorinated acid mediums. They found that stable lms of metallic copper and tin oxides were formed on the surface of steel, which led to the preferential dissolution of Cu and Sn.…”
Section: Introductionmentioning
confidence: 98%